Localkart Hyperload E-Commerce - Gaurav Nigade,; Rohan Kakade,; Abhishek Nandkhile,; Rushikesh Unde,; Prof. Joshi G. R, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Localkart Hyperload E-Commerce presents a novel mobile platform aimed at revolutionizing agricultural business processes through advanced information and communication technologies. The platform enables farmers to manage product listings, integrate real-time market rate data, and receive customer feedback, while offering customers a seamless interface for product discovery, peer reviews, and secure payment processing. Modern mobile development techniques utilizing Flutter and Dart combine with robust backend services provided by Firebase, including Authentication, Firestore. Integration of chatbot for providing help to Customers and the recommendations ensures a highly interactive and responsive user experience. By addressing technical and operational challenges inherent in digital agriculture, Android Farmer App empowers rural stakeholders and enhances overall market efficiency.
Keywords: Localkart Hyperload E-Commerce; Flutter; Firebase; Razorpay; Gemini API; Provider (State Management); Search & Sort Algorithms; Real time Market Rates; AI Chatbot